Satisfaction with vaccination services and its relationship to emotional responses of service users in Lima. LEGADO’s quality management model as a public solution to promote citizen emotional well-being during pandemic - Espinosa, Agustin; Marti, Jordi; Calderón-Prada, Alicia; Ticliahuanca, Milagros; Lobrano, Jacqueline; Carreón, Nataly (Frontiers in Public Health, 2023)
This article analyzes the levels of citizen satisfaction with LEGADO’s quality management model service during the first year of vaccination against SARS-CoV-2 in public spaces administered by LEGADO, and its relationship with the user’s emotional responses. To this end, a survey study has been developed from July 2021 until March 2022 at 4 moments to citizens (n = 1,697) who attended 3 vaccination locations administered by LEGADO (VIDENA, Complejo VMT and Polideportivo VES). The results show a high level of satisfaction with LEGADO’s quality model service, which is associated with a positive emotional balance. Specifically, the elements that have the greatest effect on positive emotions are the cleanliness and facilities’ organization and the agility of service. These results are discussed emphasizing the importance of the role of public institutions in developing inclusive quality public services for all citizens. This strategy of public quality model service according to citizens’ necessities should result in confidence towards public institutions and socially responsible behavior among citizens through the reduction of social gaps. The research establishes the urgency to promote this model in order to bring legitimacy and confidence to public institutions in Perú.